Association between serum non-high-density lipoprotein cholesterol and cognitive impairment in patients with acute ischemic stroke. Issue 1 (December 2016) - Lu, Da; Li, Pan; Zhou, Yuying; Xu, Xiaolin; Zhang, Huihong; Liu, Liping; Tian, Zhiyan
Abstract Background Non-high density lipoprotein cholesterol (HDL-C) could be a good predictor of vascular disease outcomes. To evaluate the association between serum non-HDL-C and cognitive impairment in patients with acute ischemic stroke. Methods A total of 725 hospitalized patients with acute ischemic stroke were enrolled. They received conventional treatment. Cognitive function was assessed on the 3rd day after admission using mini-mental state examination (MMSE), Montreal Cognitive Assessment (MoCA), Activity of Daily Living Scale (ADL), and Neuropsychiatric Inventory (NPI, and Hamilton depression rating scale 21-item (HAMD-21). Lipid profile and biochemical markers were measured, and non-HDL-C was calculated. Results Compared with patients with normal non-HDL-C, those with high non-HDL-C showed lower MMSE (23.1 ± 4.9 vs. 26.0 ± 4.6, P  < 0.001) and MoCA (20.4 ± 6.4 vs. 22.2 ± 5.3P  = 0.01) scores, higher NPI (6.2 ± 1.2 vs. 3.3 ± 1.5, P  < 0.001) and HADM-21 (6.0 ± 2.2 vs. 4.5 ± 1.9, P  < 0.001) scores, and higher homocysteine (16.0 ± 3.8 vs. 14.3 ± 2.0 mmol/L, P  = 0.044), fasting blood glucose (6.4 ± 2.7 vs. 6.1 ± 2.1 mmol/L, P  = 0.041), and HbA1c (6.80 ± 1.32 % vs. 6.52 ± 1.17 %, P  = 0.013) levels. MMSE (r  = -0.526, P  < 0.001), MoCA (r  = −0.216, P  < 0.001), and NPI (r  = 0.403, P  < 0.001) scores were correlated with non-HDL-C levels. High non-HDL-C levels were an independent risk factor for cognitive disorders after acute ischemic stroke (P  = 0.034, odds ratio = 3.115, 95 % confidence interval: 1.088–8.917). Conclusions High serum non-HDL-C levels, age, education, homocysteine levels, and HAMD score were independent risk factors of cognitive impairment in patients with acute ischemic stroke. The risk of cognitive disorders after acute ischemic stroke increased with increasing non-HDL-C levels. This parameter is easy to assess in the clinical setting.